2015
DOI: 10.4141/cjas-2014-142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sainfoin hay and pomegranate peel extracts on in vitro fermentation and protein degradation using the RUSITEC technique

Abstract: Effect of sainfoin hay and pomegranate peel extracts on in vitro fermentation and protein degradation using the RUSITEC technique. Can. J. Anim. Sci. 95: 417Á423. The objectives of this study were to determine the effect of supplementation of sainfoin hay extract (SHE) and pomegranate peel extract (PPE) on in vitro rumen fermentation characteristics, protein metabolism and nutrient digestibility using rumen simulation technique (RUSITEC). The experiment was a completely randomized design with three treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…suggest that the yeast additives might lead to greater fibrolytic bacteria proliferation and reduced decarboxylation of branchedchain amino acids (isoleucine, leucine, and valine), which in turn indicates that the addition of the additive at intermediate doses led to a lower degradation of these amino acids (Refat et al, 2015). Furthermore, it is important to emphasize that the tested additive provided an additional source of BCVFAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggest that the yeast additives might lead to greater fibrolytic bacteria proliferation and reduced decarboxylation of branchedchain amino acids (isoleucine, leucine, and valine), which in turn indicates that the addition of the additive at intermediate doses led to a lower degradation of these amino acids (Refat et al, 2015). Furthermore, it is important to emphasize that the tested additive provided an additional source of BCVFAs.…”
Section: Discussionmentioning
confidence: 99%
“…similar total GP observed for all treatments at the end of the fermentation baths. Likewise, in the BCVFA results, part of ruminal NH 3 -N comes from protein degradation (Refat et al, 2015). Furthermore, some rumen fibrolytic microorganisms can build their amino acids from NH 3 -N and carbon skeletons (Reynolds and Kristensen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…But, they have proposed that addition of pomegranate peel extract has decreased protozoa population, ammonia-N concentration, and increased propionate to acetate proportion and microbial protein production. Refat et al (2015) also found that supplementing high grain diets with pomegranate peel extracts in Rusitec system, results in decreasing total and branched-chain VFA and ammonia nitrogen concentration as well. They have mentioned that, the effects of plant extracts contain high polyphenolic compounds on total VFA production and individual proportion of VFA varied and mostly dependent on source, rate and dosage of polyphenolic compounds.…”
Section: Me Nel Dom Content and Scfa Productionmentioning
confidence: 81%
“…An increase in ammonia‐nitrogen production will benefit the increase in the protozoa population and the decomposition of microbial protein (Busquet et al., 2006). Nevertheless, comparison with the literature is challenging because information on the effect of pomegranate peel, seed and oil revealed a decreased concentration in rumen fluid of ammonia (Natalello et al., 2020; Refat et al., 2015; Sharifi et al., 2019). The impact of tannins on ruminal protein metabolism has been attributed to their ability to attach plant protein, decline the microbial enzyme's activity, reduce bacteria growth rate and finally decrease ruminal NH 3 ‐N (Molan et al., 2001; Min et al., 2005).…”
Section: Discussionmentioning
confidence: 99%